Investigation of the acousto‐optical properties of Ge–As–Te–(Se) chalcogenide glasses at 10.6 μm wavelength. Issue 7 (31st March 2021) - Cao, Zhenfei; Dai, Shixun; Liu, Zijun; Liu, Chengcheng; Ding, Shengjie; Lin, Changgui
Abstract: The acousto‐optic parameters of Ge10 As90− x Te x ( x  = 30, 40, 50, 60, 70 mol%) and Ge10 As20 Te70− y Se y ( y  = 20, 30, 40, 50 mol%) glasses, were studied systematically to compare the pros and cons of Te‐based and Se‐based chalcogenide glasses in acousto‐optic performance, as well as the thermomechanical properties. In the Ge10 As90− x Te x system, the acousto‐optic figure of merit (M2 ) increased with increased Te content, and the maximum M2 of 2279 × 10 −18  s 3 /g, which is 13 times that of commercial single‐crystal Ge, obtained in Ge10 As20 Te70 at 10.6 μm. However, its thermal properties and elastic modulus decreased and the acoustic attenuation ( α ) at different ultrasonic frequencies increased accordingly. In the Ge10 As20 Te70− y Se y system, the thermomechanical performance of the glasses improved with the introduction of Se element, the overall α was lower than that of Te‐based chalcogenide glasses, and the minimum α was 5.29 dB/cm at 30 MHz ultrasonic frequency, although its M2 was inferior to that of Te‐based chalcogenide glasses. Additionally, the difference in the α of these glasses was smaller at low ultrasonic frequencies than at high ultrasonic frequencies. This work will promote the practical application of chalcogenide glasses as promising materials with outstanding acousto‐optic properties in low ultrasonic frequency acousto‐optic devices.